Aquaculture Practices and Knowledge Level of Fish Farmers in Purulia District of West Bengal - Rej, Nilanjan; Dana, Shyam Sundar; Mondal, Abdul Hannan; Sarkar, Moumita Ray; Ray, Dipam; Ahammed, Arif; Karjee, Ritika (Indian Journal of Extension Education, 2025)
The study was conducted in the Purulia district of West Bengal during 2024–25, aimed to assess the state of aquaculture and the knowledge level of fish farmers. 120 fish farmers were individually interviewed to collect primary data. Most ponds were earthen (90.83%), rain-fed (68.33%), and seasonal (56.67%), with water retention for 6 to 9 months. Indian major carp were farmed by 86.67 per cent of the respondents through polyculture systems. Only 15 per cent used commercial feed, and 77.5 per cent monitored fish growth throughout the culture period. It was also revealed that 38.33 per cent had a medium level of knowledge, while 34.17 per cent had a low level of knowledge about recommended fish farming practices. It was further found that education, occupation, farming experience, mass media exposure, extension agency contacts, and economic motivation had strong relationships with the respondents’ knowledge level (p
Keywords: Constraints; Fish farmer; Knowledge level; Purulia District